Attitudes of undergraduate students to the study of french language as a general study course in Ajayi Crowther University, Oyo, Nigeria (2013)
The study examined the attitudes of undergraduate students to the study of French language as a general study course in Nigerian tertiary institutions using Ajayi Crowther University, Oyo, Nigeria as a case study. A total of 200 undergraduate students of this university constitute the sample for this study. The research adopted descriptive research design of survey type. The results show that area of specialization has influence on attitudes of students towards French language. Also, there is no significant difference between the male and female undergraduate students’ attitude towards French language. The results further revealed that there is a significant difference in students’ attitudes and the knowledge of French language. It is recommended that the Government should make French language compulsory in all tertiary institutions in Nigeria as part of efforts to make Nigeria English-French bilingual nation.